2017
DOI: 10.1080/13880209.2017.1309554
|View full text |Cite
|
Sign up to set email alerts
|

Anti-DHAV-1 reproduction and immuno-regulatory effects of a flavonoid prescription on duck virus hepatitis

Abstract: Context: The flavonoid prescription baicalin-linarin-icariin-notoginsenoside R1 (BLIN) has a curative effect on duck virus hepatitis (DVH) caused by duck hepatitis A virus type 1 (DHAV-1). However, the mechanism of this curative effect is not understood.Objective: This study investigates the mechanism of the curative effect of BLIN on DVH caused by DHAV-1. We analyzed the anti-DHAV-1 reproduction mechanism and immuno-regulatory effect of BLIN.Materials and methods: The anti-DHAV-1 reproduction effects of BLIN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Curcumin suppressed HBV via downregulation of the metabolic coactivator PGC-1 α , a starvation-induced protein that has been shown to robustly coactivate HBV transcription [ 98 ]. The flavonoid prescription baicalin-linarin-icariin-notoginsenoside R1 had curative effect on duck virus hepatitis caused by duck hepatitis A virus type 1 (DHAV-1), which could inhibit DHAV-1 reproduction by destroying its adsorption and release [ 99 ]. Quercetin significantly reduced the viral genome replication, the production of infectious HCV particles, and the specific infectivity of the newly produced viral particles [ 100 ].…”
Section: The Potential and Mechanism Of Action Of Polyphenols In Tmentioning
confidence: 99%
“…Curcumin suppressed HBV via downregulation of the metabolic coactivator PGC-1 α , a starvation-induced protein that has been shown to robustly coactivate HBV transcription [ 98 ]. The flavonoid prescription baicalin-linarin-icariin-notoginsenoside R1 had curative effect on duck virus hepatitis caused by duck hepatitis A virus type 1 (DHAV-1), which could inhibit DHAV-1 reproduction by destroying its adsorption and release [ 99 ]. Quercetin significantly reduced the viral genome replication, the production of infectious HCV particles, and the specific infectivity of the newly produced viral particles [ 100 ].…”
Section: The Potential and Mechanism Of Action Of Polyphenols In Tmentioning
confidence: 99%
“…In recent years, the research on antiviral property of Traditional Chinese Medicine has attracted the attention of research groups worldwide due to its minimal side effect and low toxicity [ 14 ]. The baicalin as a flavonoid is the metabolite of baicalein and the evidence of its antiviral role against HSV-1, Herpes simplex virus 2 (HSV-2), Zika virus (ZIKV), Influenza A virus (IAV), Duck hepatitis A virus type 1 (DHAV-1), and NDV has been reported [ 7 , 8 , 15 17 ]. In our previous study, we demonstrated that baicalin has an specific inhibitory effect on ALV-J infection by reducing the infectivity and affecting virus internalization [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the research on antiviral property of Traditional Chinese Medicine has attracted the attention of research groups worldwide due to its minimal side effect and low toxicity [11]. The baicalin as a avonoid is the metabolite of baicalein and the evidence of its antiviral role against HSV-1, HSV-2, ZIKV, IAV, DHAV-1, and NDV has been reported [4], [5], [6], [12], [13]. In our previous study, we demonstrated that baicalin has an speci c inhibitory effect on ALV-J infection by reducing the infectivity and affecting virus internalization [8].…”
Section: Discussionmentioning
confidence: 99%